Pelatihan Teknik Pemasaran Online Produk Kerajinan Pada Pusat Dakwah Komunitas Muhammadiyah - Wida Purwidianti; Tri Septin Mujirahayu (LPPM UMRI, 2020)
This article is entitled Training on Marketing Techniques of Handicraft Products at the Muhammadiyah Community Da'wah Center. Craft Product Marketing Technique Training was held on Friday, July 24, 2020 at the preaching center of the Muhammadiyah community in Srirahayu Village, South Purwokerto. The number of participants who took part in the training was 15 people. Training activities are carried out by extension and training methods. The results obtained in this activity are in the form of entrepreneurship materials, online marketing techniques and online marketing media.